Reconstruction of the Nasal Wings with the Inverted Flap Technique. Presentation of Two Cases - Raquel Rojas Bruzón; Juan Carlos Quintana Díaz; Yulexis Hechavarría Jiménez (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Nasal reconstruction was born in India, 3000 years before our era. Nasal reconstruction has followed three basic lines: the Indian method, using the median frontal flap; the French method with the lateral cheek flap; and the Italian method with the brachial flap. Flaps allow the reconstruction of defects by restoring nasal shape and function. The classic method for reconstructing the ala nasal is the nasolabial flap. The nasolabial flap has specific characteristics in terms of location, size, circulatory pattern, vascularization, innervation, and function. We present two cases of patients treated at the Princess Marina Hospital in Botswana in Africa, who required inverted nasolabial flaps for the reconstruction of their nasal wings. After the application of the procedure, the affected nasal wing was recovered, returning functionality, harmony, symmetry and order in both cases in relation to the contralateral wing in the absence of complications. The inverted nasolabial flap is useful to restore the contour of the nasal wing, as well as to support the wing and to shape the nasal floor. This flap can have a minimum of complications if the structures are handled gently and the sutures are handled without tension. That cases are presented because of how interesting this type of intervention is, carried out by Cuban specialists in their medical collaboration in an african country.